Light or Deep Pressure: Medical Staff Members Differ Extensively in Their Tactile Stimulation During Preterm Apnea - Martin, Sven; Thome, Ulrich Herbert; Grunwald, Martin; Mueller, Stephanie Margarete (Frontiers in Pediatrics, 2020)
Background: Even though tactile stimulation is common practice to terminate preterm apnea, the style and intensity of these interventions is not specified during theoretical or practical training and has never been clinically evaluated. Objective: The present study was designed to analyze the various modes of tactile stimulation used to terminate preterm apnea and measure the pressure intensity and frequency of these stimulations. Methods: A model with the size and weight of an actual preterm infant was equipped with sensor technology to measure stimulation pressure and frequency of tactile stimulation. Additionally a camera system was used to record hand positions and stimulation modes. 70 medical staff members took part in the experiment. Results: We found extreme between subjects differences in stimulation pressure that could not be explained by professional experience but, to a degree, depended on apnea intensity. Pressures ranged from 11.11 to 226.87mbar during low intensity apnea and from 9.89 to 428.15mbar during high intensity apnea. The majority of participants used rhythmic stimulation movements with a mean frequency of approximately 1Hz. Different modes (rubbing, squeezing, tickling, and tapping) and finger positions were used. Conclusion: Medical staff members intuitively adjust their tactile stimulation pressure depending on the premature infants’ apnea intensity. However, mean pressure values varied greatly between subjects, with similar pressure ranges for low and high intensity apnea. The question remains which pressure intensities are necessary or sufficient for the task. It is reasonable to assume that some stimulation types may be more effective in rapidly terminating an apneic event.